Measurement and correlation of solubility data for deferiprone in propylene glycol and 2-propanol at different temperatures - Homa Rezaei; Elaheh Rahimpour; Fleming Martinez; Abolghasem Jouyban (Heliyon, 2023)
This investigation dealt with the thermodynamic properties, saturated solubility values, and solvation behavior of deferiprone as an oral iron chelator agent in non-aqueous mixtures of propylene glycol and 2-propanol using experimental measurements and mathematical correlations. The solubility of deferiprone demonstrated a positive correlation with both temperature and propylene glycol mass fraction. Four mathematical models were employed to correlate the solid-liquid equilibrium data, and the low mean relative deviation values of less than 3.6% illustrate the good agreement of computed data with the experimental data. The apparent thermodynamic behavior of deferiprone dissolution was also investigated according to van’t Hoff and Gibbs equation.